Analisis Hukum Terhadap Tanggung Jawab Penjual atas Barang Cacat dalam Perjanjian E-Commerce - Rondo, Fiona Louysa; Lie, Gunardi (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Electronic commerce (e-commerce) has grown rapidly and become a vital part of modern economic activity. The shift from conventional to digital transactions brings many benefits, such as time efficiency, ease of access, and market expansion. However, behind these advantages, new issues have emerged, particularly regarding seller responsibilities and legal protection for consumers in the event of losses due to defective or non-conforming goods. This study uses a normative juridical method with a statutory approach, which examines the Civil Code, the Consumer Protection Law, the Electronic Information and Transactions Law, the Trade Law, and Government Regulation No. 80 of 2019. The results show that sellers have a legal obligation to guarantee that the goods sold are free from defects, in accordance with the principles of good faith and the principle of pacta sunt servanda. Consumers who are harmed have the right to obtain compensation through non-litigation mechanisms such as refunds, returns, mediation, or arbitration, as well as litigation in court. Marketplaces also play a significant role in providing consumer protection through escrow systems, return policies, and complaint services. Although regulations exist, their implementation still faces challenges such as weak oversight, difficulties in providing evidence, and legal loopholes. Therefore, strengthening regulations, increasing oversight, and utilizing online dispute resolution technology are necessary to effectively protect consumer rights in the digital age